Neurotheology in Law: The Dichotomy of Religion and Neuroscience in the Legal Field - Ruszkowski, Kelsey R. (A journal of church and state, 2021)
Introduction Although the United States does not have an established religion, it has provided religious practice broad protection under the Free Exercise Clause.1 After the passage of the Religious Freedom Restoration Act, courts started to strictly scrutinize laws that interfere with religious practice.2 Now religious practitioners can challenge such laws on substantive due process and equal protection grounds.3 The Free Exercise Clause provides exceptions in a variety of areas including health and education.4 In some areas, practitioners cannot only claim exceptions for themselves but also assert them on behalf of their minor children.5 Unfortunately, these exceptions can have long-term and far-reaching effects for those children.6 These effects can result in physical and developmental injuries that can have adverse consequences such as limiting employment prospects and impeding self-autonomy.7 Because of this, courts must balance the practitioner’s religious practice with the government’s interest in welfare and...